A bibliometric and visual analysis of postburn hand reconstruction - Shenying Luo; Hsin Liang; Bin Gu; Tao Zan; Jieyi Ren (Chinese Journal of Plastic and Reconstructive Surgery)
Background: Scar contractions caused by hand burns seriously impact both the function and appearance of the hand. Consequently, post-burn hand reconstruction is a primary focus of secondary reconstructive surgery performed within the first 10 years after a burn injury. This study aimed to identify developmental trends and research hotspots in post-burn hand reconstruction, providing insights and recommendations for researchers. Methods: Bibliometric and visualization analyses were conducted using CiteSpace v6.4. R1 (64-bit) and VOS viewer. The Web of Science Core Collection served as the data source. A total of 136 articles between 1997 and 2025 were included based on the following keywords: “postburn hand reconstruction” or “postburn hand” or “scar contraction hand deformity.” Results: The field of post-burn hand reconstruction is advancing, as indicated by the overall and annual increase in publications. The United States leads in number of published papers. However, major institutions show low centrality, indicating weak collaboration between countries and regions, with research still dominated by single-center studies. The top three most prolific authors were Paul P M van Zuijlen, Fatih Uyghur, and Ersin Uyghur. The keywords “double Z-plasty” and the cluster “flap” not only have high emergence intensity but also appear frequently in recent studies, marking them as current research hotspots. Conclusion: The lack of long-term research and consensus limits further advancements in post-burn hand reconstruction. To address this, multi-center and multi-disciplinary collaborations should be encouraged. Additionally, integrating basic medical research with biomedical engineering could enhance the management and outcomes of post-burn hand reconstruction.